Almost Paracontact 3-Submersions (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, we discuss some geometric properties of Riemannian submersions whose total space is an almost paracontact manifold with 3-structure. The study is focused on the transference of structures, the geometry of the fibres and sectional curvature tensor.